2014
DOI: 10.5897/ajar2013.7665
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of climate-smart agriculture in combating climate change, desertification and improving rural livelihood in Northern Nigeria

Abstract: Worldwide emphasis has been placed on designing approaches with regard to the needs of sustainable development. Climate-Smart Agriculture (CSA) is one key agricultural development approach aimed at sustainably increasing productivity and resilience, while also reducing/removing emissions of greenhouse gases. Although many countries will be expected to adopt this approach, its applicability in an African context is not very clear, well studied nor has its sustainability been assessed. We used the Sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Climate-smart agriculture, as a concept, is aimed at helping farmers adjust to climate change and minimize its plausible unfavorable effect on their agricultural activities and livelihoods [27]. However, past experiences have revealed that some recommended innovations have been discovered not to be applicable in many developing countries after such innovations have been adopted [30].…”
Section: Introductionmentioning
confidence: 99%
“…Climate-smart agriculture, as a concept, is aimed at helping farmers adjust to climate change and minimize its plausible unfavorable effect on their agricultural activities and livelihoods [27]. However, past experiences have revealed that some recommended innovations have been discovered not to be applicable in many developing countries after such innovations have been adopted [30].…”
Section: Introductionmentioning
confidence: 99%
“…Following the Second Global Conference on Agriculture, Food Security and Climate Change in Hanoi in 2012, "Climate-Smart Agriculture Sourcebook" was published to further advance the concept with the intention of benefiting primarily smallholder farmers and vulnerable people in developing countries (FAO, 2013). In the work of Fanen and Olalekan (2014) on "Assessing the role of Climate-Smart Agriculture in combating climate change, desertification and improving rural livelihood in Northern Nigeria", they have found out that many smallholder farmers have inadvertently practiced CSA as part of their traditional farming system in Northern Nigeria. This study therefore seeks to identify the extent of use of CSAPs and also to determine the factors influencing their level of usage in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Boosting crops yield per unit area may be the grand strategy. Adoption of climate-smart agricultural (CSA) practices and technologies such as the use of high yielding seeds/genetically modified organisms (GMO), use of modern farm inputs, inorganic and organic fertilizers, herbicides and pesticides (Terdoo and Adekola, 2014;FAO, 2010). Others policies may focus on supporting and building capacity of farmers in the state to access farming inputs and loan facilities, designing and implementing programmes and projects aim at adding value to output of crops as well as increase farmers access to markets and tackling uncertainties in climate arising from reduced rainfall and increasing temperatures (Dawson et al, 2016;Grassini et al, 2013;Nin-Pratt and McBride, 2014).…”
Section: Discussionmentioning
confidence: 99%